The Effectiveness of international law in resolving climate change disputes: Case law, compliance, and equity perspectives - Saif Saad Ahmed; Zahraa Ghazi Sadiq; Ali Ghassan Ahmed Mohammed; Zahraa Mahdi Dahsh; Ammar Abdulkhaleq Ali (Environment and Social Psychology, 2025)
Climate change generates important worldwide problems which lead nations to disagree about responsibility allocation and both reduction efforts and policy course change. International law stands as the main factor in the advancement of cooperative solutions and conflict resolution of these matters. The article investigates how foreign law enables climate change disputes resolution while maintaining their effectiveness and adaptability and their ability to support sustainable solutions among stakeholders. The study reviewed international legal documentation starting from treaties and conventions together with judicial decisions. Case studies that examined important climate change-related issues served as the primary focus of research to determine global legal system effectiveness. In total, 250 environmental cases from international courts, arbitration bodies, and regional tribunals were examined, alongside 50 UNFCCC documents. The analysis applied both qualitative and quantitative methods, including compliance gap, equity index, dispute resolution effectiveness, and mitigation efficiency models, to measure the performance of international law in addressing climate disputes. The article demonstrates that state accountability functions alongside non-governmental groups and compliance verification systems prove highly crucial to the process. The study demonstrates that international law expedited the resolution of climate change problems through improved dialogue which drove consensus. Performance delivery suffers from recurring issues mainly because of unequal representation for less-developed nations and non-contractual commitment levels. Findings highlight persistent compliance gaps across major emitters, moderate effectiveness of judicial and arbitral bodies, and inequitable burden-sharing between developed and developing countries. Landmark cases such as Urgenda v. Netherlands and Juliana v. United States illustrate both the potential and limitations of climate litigation. The authors highlight the significance of the UN Framework Convention on Climate Change together with the Paris Agreement to guide international projects. Through its structured dispute settlement structure international law enables proper management of climate change issues. Sustainable climate change solutions through equitable outcomes become achievable with stronger legal systems combined with better compliance enforcement mechanisms.